Whole-genome sequencing analysis of the cardiometabolic proteome - Arthur Gilly (Nature Portfolio, 2020)
The human proteome represents a crucial link between complex disease and genetic/environmental factors. Here, the authors investigate 257 cardiometabolic-relevant protein biomarkers in whole genome sequencing data from 1328 individuals, revealing the genetic architecture underlying biomarker variation.